"The Quiet Revival": New Immigrants and the Transformation of Christianity in Greater Boston. Issue 2 (18th June 2014) - Johnson, Marilynn
Abstract: In the years after 1965, a new wave of Asian, Latino, Caribbean, and African immigrants has transformed and revitalized the religious landscape of many U.S. cities. This essay explores the transformation of Christianity in greater Boston, where new immigrants replenished ailing congregations and infused them with new religious and social practices. This de-Europeanization of Christianity was not simply a result of transnational practices but resulted from a collaborative process between immigrants and native-born religious institutions. Both Catholic and Protestant churches experienced this immigrant-based revitalization, but evangelical Protestants have been particularly adept at partnering with newcomers to promote a "quiet revival" of urban Christianity.